FAKTOR-FAKTOR YANG MEMPENGARUHI PENGHINDARAN PAJAK PADA PERUSAHAAN NON-KEUANGAN DI BURSA EFEK INDONESIA - Joan Vincenza Putri; Ferry Suhardjo (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
Abstract - This study aims to obtain empirical evidence and analyze factors that affecting tax avoidance. The independent variables in this study are foreign ownership, independent commissioner, institutional ownership, leverage, firm size, and profitability. While the dependent variable in this study is tax avoidance. The object of research used in this research is non-financial companies that are consistenly listed on the Indonesia Stock Exchange (IDX) from 2018 to 2020. The form of sampling used in this study is the purposive sampling method, where the sample selection is based on certain criteria. The number of sample selections that successfully meet the criteria are 136 companies with total of 408 data. This study uses multiple regression method to examine the effect of the independent variable on the dependent variable of tax avoidance. The result of this study shows that foreign ownership and firm size have an effect on tax avoidance. The more foreign ownership of a company, the lower the company’s tax burden, which leads to lower corporate tax avoidance practices. This is because foreign investors actively support a greater corporate responsiveness to society’s needs by paying a higher tax rates. The size of the company has an effect on tax avoidance. This is because larger companies have more complex transactions than smaller companies, so companies will have a tendency to take advantage of existing loopholes to avoid taxes. Meanwhile, independent commissioners, institutional ownership, leverage, and profitability have no effect on tax avoidance.